Association between dietary patterns and overweight and obesity among primary and middle school students - JIANG Nan, TANG Xiaomin, SUN Wentao (预防医学)
Objective: To explore the association between dietary patterns and overweight and obesity among primary and middle school students, so as to provide the guidance of diet balance and obesity prevention for students. Methods: Students from 11 primary and middle schools in Tongzhou District, Beijing Municipality, were selected using the stratified cluster sampling method. Demographic information was collected through a general questionnaire, and dietary intake types and frequencies over the past week were assessed using a food frequency questionnaire. Dietary patterns were determined using factor analysis, and the dietary pattern factor scores were divided into Q1, Q2, Q3, and Q4 groups based on quartiles. Height and weight were collected through physical examinations, and Z-scores of body mass index adjusted for gender and age were calculated to assess overweight and obesity. The association between dietary patterns and overweight and obesity was analyzed using a multivariable logistic regression model. Results: A total of 1 485 students were surveyed, including 745 males (50.17%) and 740 females (49.83%). The mean age was (12.87±2.86) years. Three dietary patterns were identified: animal and plant protein dietary pattern, high-fat and high-sugar dietary pattern, and vegetable-fruit-dairy dietary pattern. The detection rates of overweight and obesity were 42.57%, 48.42%, and 34.75%, respectively, with statistically significant differences (P<0.05). Multivariable logistic regression analysis showed that compared with the vegetable-fruit-dairy dietary pattern, the animal and plant protein dietary pattern (OR=1.406, 95%CI: 1.084-1.823) and the high-fat and high-sugar dietary pattern (OR=2.137, 95%CI: 1.643-2.779) were associated with a higher risk of overweight and obesity among primary and middle school students. Compared with the Q1 group of dietary pattern factor scores, the Q3 group (OR=1.631, 95%CI: 1.206-2.208) and Q4 group (OR=1.965, 95%CI: 1.446-2.671) of the high-fat and high-sugar dietary pattern had an increased risk of overweight and obesity, while the Q4 group of the vegetable-fruit-dairy dietary pattern (OR=0.551, 95%CI: 0.406-0.747) had a reduced risk of overweight and obesity. There was no statistical association between factor scores of animal and plant protein dietary pattern and overweight and obesity (all P>0.05). Conclusions: The animal and plant protein dietary pattern and the high-fat and high-sugar dietary pattern are associated with a higher risk of overweight and obesity among primary and middle school students. Within the same dietary pattern, the more inclined students are to the high-fat and high-sugar dietary pattern, the higher their risk of overweight and obesity, while the more inclined they are to the vegetable-fruit-dairy dietary pattern, the lower their risk of overweight and obesity.